METODE PENDIDIKAN ISLAM (Tela‟ah Pemikiran Abdul Wahab asy-Sya‟rāni) - Subaidi Subaidi (Intelegensia : Jurnal Pendidikan Islam, 2014)
Abstract: This study aims to describe the application of the Islamic education methods offered by Abdul Wahab asy-Sya'rāni. The focus of this research is to determine the methods of Islamic education, among others; (1) knowing effective educational methods, (2) knowing the Islamic education methods of Abdul Wahab asy-Sya'rāni. The method used in this research is interpretive research. The results of this study include four methods of Islamic education, among others: 1) the at-Tadrīj method, 2) the al-uswah method (exemplary) and habituation, 3) the story method, and 4) the advice method.Keywords: methods; Islamic education